Greek and Latin Astrological Poetry Reconsidered - Heilen, Stephan (Aestimatio, 2023)
A discussion of La poésie astrologique dans la littérature grecque et latine by Vanessa Monteventi that contextualizes this meritorious yet imperfect monograph in modern research on ancient astrological poetry and focuses on the whole range of its philological, astronomical, and astrological aspects. It is shown that Monteventi’s title promises a broader perspective than what her book actually covers. A more fitting title would be La poésie didactique astrologique dans la littérature grecque et latine de l’Antiquité. Numerous poems relevant to her actual title yet not taken into account by the author are collected here for the first time ever without any pretense to completeness [see Appendix 2, p. 62], and their relevant characteristics briefly sketched, including discussions of two anything but trivial mathematical riddles contained in anonymous astrological poems. Besides a plethora of details that call for minor addenda/corrigenda, a few of Monteventi's topics are discussed in depth, such as the autobiographical horoscope by the first didactic poet writing under the pseudonym of Manetho and the sources of the smaller astrological poem by John Camaterus.